Kebutuhan Lansia dalam Menghadapi Bencana: Studi Fenomenologi - Lucky Albertus Palenewen; Fidy Randy Sada; Cornelia Fransiska Sandehang; Johanis Kerangan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Older adults are among the most vulnerable populations in disaster situations due to physical, psychological, social, and economic limitations that may exacerbate disaster impacts, including injury, psychological distress, and death. Disasters affect not only the physical safety of older adults but also their emotional and psychological well-being, highlighting the need for disaster management approaches that are sensitive and specialized. This study aimed to explore the needs of older adults in disaster situations. A qualitative study with a phenomenological approach was conducted. Data were collected through in-depth interviews with eight participants who were directly involved in the management and care of older adults during disasters. Data analysis was performed using Colaizzi’s method. The findings revealed four main themes: (1) the need for age-friendly evacuation facilities and infrastructure; (2) limitations in human resources during the evacuation process; (3) the need for health and psychosocial support services, particularly for older adults with cognitive impairments; and (4) the need for institutional and policy support. These findings indicate that the needs of older adults in disaster contexts are multidimensional and interrelated. Therefore, inclusive and integrated disaster management strategies that are oriented toward the specific needs of older adults are essential to enhance their safety, preparedness, and overall well-being during disaster situations.